Physical exercise shapes the mouse brain epigenome - Rocío G. Urdinguio; Juan Ramon Tejedor; Manuel Fernández-Sanjurjo; Raúl F. Pérez; Alfonso Peñarroya; Cecilia Ferrero; Helena Codina-Martínez; Carlos Díez-Planelles; Paola Pinto-Hernández; Juan Castilla-Silgado; Almudena Coto-Vilcapoma; Sergio Díez-Robles; et al. (Elsevier, 2021)
Objective: To analyze the genome-wide epigenomic and transcriptomic changes induced by long term resistance or endurance training in the hippocampus of wild-type mice. Methods: We performed whole-genome bisulfite sequencing (WGBS) and RNA sequencing (RNA-seq) of mice hippocampus after 4 weeks of specific training. In addition, we used a novel object recognition test before and after the intervention to determine whether the exercise led to an improvement in cognitive function. Results: Although the majority of DNA methylation changes identified in this study were training-model specific, most were associated with hypomethylation and were enriched in similar histone marks, chromatin states, and transcription factor biding sites. It is worth highlighting the significant association found between the loss of DNA methylation in Tet1 binding sites and gene expression changes, indicating the importance of these epigenomic changes in transcriptional regulation. However, endurance and resistance training activate different gene pathways, those being associated with neuroplasticity in the case of endurance exercise, and interferon response pathways in the case of resistance exercise, which also appears to be associated with improved learning and memory functions. Conclusions: Our results help both understand the molecular mechanisms by which different exercise models exert beneficial effects for brain health and provide new potential therapeutic targets for future research.